Adherence to healthcare waste management protocols in selected health facilities, Greater Accra and Eastern Regions, Ghana, 2021 - Benjamin Osei-Tutu; Rita Agyekumwah Kusi Asante; Ernestina Esinam Agbemafle; Doreen Danso; Eric Asante; Isaac Kporha; Jonathan Elikem Avunyitor; Kate Gyimaa Asante; Mark Owusu; Oxwell Opoku Sarpong; Paul Twene; Reuben Kennedy Atepre; et al. (Discover Environment, 2025)
Abstract Background Managing healthcare waste is crucial for infection prevention and control. The World Health Organization targets proper management of the 15% infectious waste generated in healthcare settings. We examined adherence to proper healthcare waste management in two regions of Ghana and its predictors to improve occupational health and safety. Methods A cross-sectional study assessed 104 health facilities in the Greater Accra and Eastern Regions of Ghana in 2021. A checklist was adapted from the WHO/UNICEF Water and Sanitation for Health Facility Improvement tool. Data was collected using interviews, observation and records review. Adherence levels were categorized as < 50% score being low, 50%–79% as medium and ≥ 80% as high. Descriptive and inferential analyses were done with significance considered at 95% confidence level and results presented using texts, tables and charts. Results Of 104 facilities, majority, 54.8% (57/104) were in Greater Accra with 45.2% (47/104) in Eastern Region. Across the two regions, Community-Based Health Planning and Services (CHPS) Compounds were 38.4% (40/104) with 26.9% (28/104) of facilities having high adherence to healthcare waste management protocols. Factors that influenced adherence included availability of placenta pit (AOR = 27.28, CI: 3.09–240.64), having PPEs (AOR = 9.52, CI: 1.27–71.24) and presence of colour coded waste bins (AOR = 16.63, CI: 1.28–216.31). Conclusion Adherence to HCWM protocols was low among facilities in Eastern and Greater Accra regions. Factors that influenced adherence were related to availability of logistics. Health facility heads should ensure the availability of waste management logistics to ensure high-level adherence to waste management protocols.